Analyses of tool life and surface roughness during hard turning of AISI H13 hot work tool steel using mixed ceramic tools - 399630 Tan, Poh Lai (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Master of Mechanical Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2003